Collaborative Care Management Reduces Disparities in Dementia Care Quality for Caregivers with Less Education - Brown, Arleen F. (2013)
BACKGROUND: Lower educational attainment among informal caregivers’ may be associated with poorer outcomes for patients with dementia. OBJECTIVE: To examine educational gradients in dementia care and whether the effect of a dementia collaborative care management intervention varied by the educational attainment of the informal caregiver. DESIGN: Analysis of data from a cluster-randomized controlled trial. SETTING: Eighteen clinics across 3 healthcare organizations in Southern California. PARTICIPANTS: Dyads of Medicare recipients, ages 65 years and older with a diagnosis of dementia, and an eligible caregiver. INTERVENTION: Collaborative care management for dementia. MEASUREMENTS: 1) Caregiver educational attainment, 2) adherence to four dimensions of guideline-recommended processes of dementia care: Assessment, Treatment, Education/Support, and Safety pre- and post-intervention, and 3) the adjusted intervention effect (IE) for each dimension stratified by caregiver education. Each IE was estimated by subtracting the difference between pre- and post-intervention scores for the usual care participants from the difference in the intervention participants. RESULTS: At baseline, caregivers with lower educational attainment had lower guideline-recommended processes of dementia care for the Treatment and Education dimensions than those with more education. However, less educated caregivers had significantly more improvement after the intervention on the Assessment, Treatment, and Safety dimensions. The IEs for those who had not graduated from high school compared to college graduates were 44.4 vs. 29.5 for the Assessment dimension (P<0.001), 36.9 vs. 15.7 for the Treatment dimension (P<0.001), and 52.7 vs. 40.9 for the Safety Dimension (P<0.001). CONCLUSIONS: Collaborative care management was associated with reductions in disparities in dementia care quality among caregivers with lower educational attainment relative to more educated caregivers.